2016
DOI: 10.1016/j.ifset.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultraviolet light assisted titanium dioxide photocatalysis for food safety: A review

Abstract: UV-assisted TiO 2 photocatalysis (TUV) is an emerging non-thermal technology that has shown to efficiently inactivate food-borne pathogens. While TUV processing has been a wellestablished technique for water and wastewater treatment, its application in the food industry is minimal. The basic working principle underlying TUV technology is the photocatalytic production of reactive oxygen species (ROS) that carry out redox reactions with species adsorbed on the TiO 2 surface. Studies have confirmed that severe ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 95 publications
0
37
0
1
Order By: Relevance
“…TiO 2 has also become the preferred photocatalyst for a variety of reasons, which include its low cost, chemical stability, non-toxicity and effectiveness under near-ultraviolet light (300–400 nm). It is one of the most applied nanomaterials and is widely used as additive in food and non-food applications [ 28 , 29 , 30 ]. Other TiO 2 nanostructures have been already developed with antimicrobial goals.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 has also become the preferred photocatalyst for a variety of reasons, which include its low cost, chemical stability, non-toxicity and effectiveness under near-ultraviolet light (300–400 nm). It is one of the most applied nanomaterials and is widely used as additive in food and non-food applications [ 28 , 29 , 30 ]. Other TiO 2 nanostructures have been already developed with antimicrobial goals.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms in package possess a great threat to the safety of fresh perishable food, and TPC technique is proved to be effective for inactivating microorganisms in foods (Ramesh, Nayak, Amirbahman, Tripp, & Mukhopadhyay, 2016). Foster et al (2011) reported that TPC had the ability to inactive most microorganisms, including gramnegative and grampositive bacteria.…”
Section: Antibacterial Activity Of Tio 2 /Nwf-8 Inpackagementioning
confidence: 99%
“…Nano‐sized TiO 2 was reported to kill viruses including poliovirus‐1 (Watts and others ), hepatitis B virus (Zan and others ), herpes simplex virus (Hajkova and others ), and MS2 bacteriophage (Cho and others ). Most recently, Ramesh and others () provided an overview of the potential applications of TiO 2 photocatalysis in the food sector. TiO 2 has been approved by the U.S. FDA for use in human food, drugs, cosmetics, and food contact materials (FDA ).…”
Section: Introductionmentioning
confidence: 99%